Drug resistance of M. tuberculosis (historical aspects, current level of knowledge) - I. A. Burmistrova; A. G. Samoylova; T. E. Tyulkova; E. V. Vaniev; G. S. Balasanyants; I. A. Vasilyeva (Туберкулез и болезни лёгких)
The review presents data on the frequency of detection of drug resistant (DR) tuberculosis mycobacteria (MTB) as well as on the change in DR patterns in Russia and abroad from the mid-50s of the 20th century till the present. Along with the well-known mechanisms for DR MTB development, it tells about new research describing mutations associated with drug resistance.